Adsorption of tebuthiuron on hydrochar: structural, kinetic, isothermal, and mechanistic modeling, and ecotoxicological validation of remediative treatment of aqueous system - Moreira, Bruno Rafael de Almeida [UNESP]; Cruz, Victor Hugo [UNESP]; Barbosa Júnior, Marcelo Rodrigues [UNESP]; de Vasconcelos, Leonardo Gomes; da Silva, Rouverson Pereira [UNESP]; Lopes, Paulo Renato Matos [UNESP] (Springer Nature, 2023)
Tebuthiuron (C9H16N4OS) offers farmers a cost-effective chemical solution to control weeds. Nevertheless, it can manifest as a hazardous organic compound to society and the environment as it escapes from agroecosystems into the surroundings via leaching and running off, polluting surface and underground water bodies. Hence, research was designed to analyze whether hydrochar can develop an adsorbent to remove it from an aqueous solution. Food waste was reacted with subcritical water at a stoichiometric 1:4 ratio (m v−1) and 1.5 M potassium hydroxide (KOH) at 10 g L−1 at 250 °C and 1.5 MPa for 2 h to produce porous hydrochar via simultaneous hydrothermal carbonization and chemical activation. The product at 25, 50, and 100 mg L−1 was tested for its ability to adsorb tebuthiuron (TBT) at 0.5, 1, and 1.5 mg L−1 by spectrophotometry. In addition, kinetic and isothermal models were applied to experimental data to describe the separation of the pollutant from the liquid-phase analytical environment. Equally significant, an ecotoxicological assay was developed to investigate its remediative potential; Lactuca sativa was employed as a testing organism, as it is responsive to TBT at phytotoxic residual quantity. Hydrochar significantly separated TBT from aqueous media. Such honeycomb-structured mesoporous carbonaceous matrix developed approximately 1420.1 m2 g−1 specific surface area and 0.05 cm3 g−1 total pore volume; hence, at the highest concentration, it adsorbed 98.65% of TBT at 1.5 mg L−1 through physical (e.g., pore filling and interparticle diffusion) or chemical (e.g., H-bonding, π-stacking, and metal-adsorbate complex) forces. In addition, it allowed seven adsorption-desorption cycles with 80% efficiency, supporting excellent regenerability. Equally significant, L. sativa germinated 76.6% on plates containing residual solution from sorption testing, validating the hydrochar for environmental bioremediation. Hence, it can advance the field’s prominence in treating TBT by bioadsorption. It can offer stakeholders across agroindustries possibilities to remediate such a compound in aquatic environments, such as water and wastewater. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Bioremediation; Hazardous organic compound; Municipal solid waste; Phenyl-urea herbicide; Porous material